Optimization Of Msmes Marketing Using Whatsapp - Sanitias Sanitias; Muhammad Dani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Covid-19 has paralyzed the economic sector, both small, medium and large scale businesses. Therefore, it takes awareness of all parties, to be able to collaborate with each other in strengthening economic activities. This service is carried out as a form of contribution to the world of education to the problems faced by the community. Service activities focus on providing digital marketing knowledge, as an alternative for MSME businesses in the midst of the covid 19 pandemic. The method of activity is in the form of training and mentoring, how to use the WhatsApp digital application for business activities. PKM activities are carried out on MSME business actors in the city of Depok. The result of this activity is knowledge in utilizing digital applications as a means of marketing MSMEs during the pandemic. Then, this activity helps MSME actors to market their products digitally through the use of the WhatsApp application.